ANALISIS PENGARUH KUALITAS AUDITOR DAN TATA KELOLA PERUSAHAAN TERHADAP FEE AUDIT: (Studi Kasus pada Perusahaan LQ45 Sektor Manufaktur di Indonesia yang Terdaftar di Bursa Efek Indonesia Periode 2019-2021) - Giovani Anggasta; Melisa Anggraini; Indra Sukma Subagio (Fakultas Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of audit quality and corporate governance on audit fees. The population in this study are LQ-45 Manufacturing Sector Companies in Indonesia Listed on the Indonesia Stock Exchange for the 2019- 2021 Period. The sample selection in this study used purposive sampling method and the research sample obtained was 81 samples. The data source used is secondary data. Based on multiple linear regression analysis using the SPSS 26.0 program, it was found that audit quality had a positive and significant effect on audit fees. Meanwhile, corporate governance has no and no significant effect on audit fees